Safety in a manufacturing company - Marian Kopczewski; Tomasz Smal (Foundations of Management, 2017)
The safety systems include the functioning of the institutions of a state, central, and local government, businesses, and social organizations. Research in this discipline should contribute to the development of the theoretical foundations and systems of national and international security and operating systems in the area of technical safety. Technical safety engineering should deal with a design, build, operation, and decommissioning of technical measures in order to minimize the opportunities and the size of their negative impact on the environment, people, and the good of civilization. With this in mind, the main purpose of the research was to evaluate the safety of technical manufacturing company that uses a wide machine park. A plant manufacturing parts and components for automobiles was the audited company.
Keywords: 650; manufacturing company; safety measures; risk analysis; safety precautions